2021
DOI: 10.1177/1758835920980558
|View full text |Cite
|
Sign up to set email alerts
|

Lorlatinib in pretreated ALK- or ROS1-positive lung cancer and impact of TP53 co-mutations: results from the German early access program

Abstract: Introduction: We report on the results of the German early access program (EAP) with the third-generation ALK- and ROS1-inhibitor lorlatinib. Patients and Methods: Patients with documented treatment failure of all approved ALK/ROS1-specific therapies or with resistance mutations not covered by approved inhibitors or leptomeningeal carcinomatosis were enrolled and analyzed. Results: In total, 52 patients were included [median age 57 years (range 32–81), 54% female, 62% never smokers, 98% adenocarcinoma]; 71% an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Similarly, in ALK translocated NSCLC, it is well known that TP53 mt+ impact PFS and OS, an effect which is independent of the ALK fusion variant (21,22). In a recent analysis with the 3 rd generation ALK inhibitor Lorlatinib, it was shown that TP53 mt+ impact significantly on PFS and OS therefore underlining the overriding effect of TP53 mt+ on the effectiveness of the 3 rd generation ALK inhibitor (23).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in ALK translocated NSCLC, it is well known that TP53 mt+ impact PFS and OS, an effect which is independent of the ALK fusion variant (21,22). In a recent analysis with the 3 rd generation ALK inhibitor Lorlatinib, it was shown that TP53 mt+ impact significantly on PFS and OS therefore underlining the overriding effect of TP53 mt+ on the effectiveness of the 3 rd generation ALK inhibitor (23).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as in other publications, several treatment discontinuations were observed following cognitive or mood disorders, highlighting the difficulty of managing this type of toxicity, which may also be exacerbated by the high frequency of brain metastases and prior radiation therapy. 14,15 In our study, we were able to analyze the subsequent therapies received after lorlatinib progression. Although significant efficacy of pemetrexed-based chemotherapy has been reported in ROS1þ NSCLC, data are lacking regarding the value of systemic treatment after lorlatinib failure.…”
Section: Discussionmentioning
confidence: 99%
“…), of the targeted therapy or the immuno/chemotherapy responsiveness and the follow‐up of the disease is a major challenge for the better understanding of NSCLC. Notably, it is essential to look for the different concurrent genomic alterations, notably TP53 mutations, in NSCLC showing a gene fusion 31,171–174 . This may lead to the development of new therapeutic strategies in the future.…”
Section: Technical Aspects Of Gene Fusion Detection In Lung Cancer: T...mentioning
confidence: 99%
“…Notably, it is essential to look for the different concurrent genomic alterations, notably TP53 mutations, in NSCLC showing a gene fusion. 31,[171][172][173][174] This may lead to the development of new therapeutic strategies in the future. So, a longterm vision of integration of NSCLC associated with a gene fusion is of strong interest.…”
Section: Management Of a Global Complex Genomic Signaturementioning
confidence: 99%